UPAYA PENINGKATAN KADAR HEMOGLOBIN REMAJA PUTRI SMK WIDYA PRAJA UNGARAN PADA PEMBERIAN KUDAPAN BERBASIS TEPUNG TEMPE - Arintina Rahayuni; Astidio Noviardhi; Dyah Nur Subandriani (Poltekkes Kemenkes Semarang, 2020)
Background : Anemia is a nutritional problem in Indonesia which was characterized by a condition where the red blood cells or hemoglobin levels is lower than the normal value. Nutritional anemia is caused by deficiency nutrients that play a role in the formation of hemoglobin, due to inadequate consumption or absorption disorders. These nutrients are iron, protein, vitamin B12 which act as catalysts in hem synthesis in hemoglobin molecules, vitamin C, zinc which affect iron absorption and vitamin E which affect the stability of the red blood cell membrane. Most of these are iron nutrient anemia. Females adolescent are more susceptible to anemia compared than men. The minimum of hemoglobin levels in females adolescent to diagnose as anemia is when hemoglobin levels are less than 12 g / dl.Objective : To increase hemoglobin levels of females adolescents by providing tempeh flour-based snacksMethod : In this study, an attempt had made to create tempe-based formula in the form of pizza which was high in iron and protein, the availability of tempe flour was great because the absorption disturbing agent was damaged by the fermentation process. The analysis was carried out to observe the difference in Hb levels in the treatment group (given tempe flour pizza) and control (given a regular pizza) and the relationship between BMI, nutrients-intake and consumption compliance with Hb levels.Result : The results showed there was an increase in Hb levels of 1.21 g% in the treatment group (61.54%). Nevertheless, the increase did not statistically significant. There was no relationship between BMI, nutrients intake and compliance with pizza consumption to increase Hb levels.Conclussion : Administration of tempeh fluor-based pizza for a month could increase Hb levels by 1.21 g/dl in most study participant, but it did not statistically significant.